Emotions and Incentives - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
We introduce a concept of emotions that emerge when workers compare their own performance with a given standard or with the performances of co-workers. Assuming heterogeneity among the workers the interplay of emotions and incentives is analysed by focusing on three incentive schemes that are frequently used in practice: tournaments, bonuses and piece rates. We identify certain conditions under which emotions lead to additional incentives and under which the employer benefits from emotional workers. Furthermore, the concept of emotions is used to explain puzzling results from laboratory and field experiments. Finally, the results provide some insights on an employer's possible preferences in favor of heterogeneous instead of homogeneous work groups.
Keywords: M5; J3; 330; bonuses; emotions; incentives; piece rates; tournaments; Leistungsanreiz; Emotion; Leistungsorientierte Vergütung; Experiment